(untitled) (Journal of Business Management and Accounting, 2019)
Islamic banks should continue to have less risky capital structure in order to maintain their sustainability and profitability. High risk capital structure tend to exposes Islamic banks to bankruptcy. Previous studies have focused on leverage in public listed companies and conventional banking but scanty studies focus on Islamic banks in Malaysia. Islamic banks are growing rapidly nowadays. The objective of this study is to develop a conceptual model on the influence of board governance characteristics and managerial ownership on leverage among Islamic banks in Malaysia. Thus, the study fills an important gap in board governance studies as many areas have not been explored, particularly, female directors and director’s meeting attendance and their association with leverage in Islamic banks. It is appropriate to look at the application of the agency theory in the perspective of capital structure decisions.